ROLES OF PARENTS IN ONLINE LEARNING DURING COVID-19 PANDEMIC - Rahmat Bason; Meida Rabia Sihite; Linda Astuti Rangkuti (EXCELLENCE: Journal of English and English Education, 2022)
The objective of the study was to find out the roles of parents in online learning of English subject during the Covid-19 pandemic. This study was conducted at SMK SPP SNAKMA Muhammadiyah Tanjung Anom during academic year 2021-2022. Descriptive qualitative research design was used to figure out the problems, namely (1) parents’ roles in guiding children and (2) how parents’ guide their children in online learning of English subject during the Covid-19 pandemic. The instrument employed in this study was interview sheet. The subjects of the study were the students’ parents and the English teachers. The first problem was answered through the analysis of interview result and found out that there were 5 roles of parents in guiding their children during online learning of English subject. The roles were as an educator (17%), as a driving force (25%), as a role model (0%), as friend (8%), as a supervisor (42%) and as a counselor (8%). The role of parents as supervisor was the dominant role found in online learning of English subject during the Covid-19 pandemic. The second problem was answered as well through the analysis of interview sheet and it was obtained that the parents’ roles in guiding the children in online learning were still low. The students’ parents had low understanding and background education regarding the implementation of online learning by their children.